[Afisz. Incipit] Wielka zabawa taneczna przed-adwentowa w sali Stoczni nr 1 ... (Gdańsk : [wydawca nieznany], 1947)
Afisz informujący o zabawie 29.11.1947 r.
Keywords: Stocznia Gdańska -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Druki ulotne -- 1945-1970.